Stakeholder perspectives on factors that influence global prioritization for MNH in humanitarian settings - Adler, Alicia; Kozuki, Naoko; Mothupi, Mamothena (Frontiers in Global Women's Health, 2024)
Background Maternal and newborn mortality rates are disproportionately high in crisis and conflict-affected countries. This study aims to understand factors influencing how MNH in humanitarian and fragile settings (HFS) is prioritized on the global health agenda during the Sustainable Development Goal (SDG) era. This includes examining the policies and processes driving agenda setting and decision-making, as well as the perceptions of global actors. It further reflects on the role of global milestones, reports, convenings, and high-level champions, based on the premise that global prioritization leads to increased attention and resource allocation, ultimately contributing to improved outcomes for mothers and newborns in crisis-affected areas. Methods A qualitative study conducted from April 2022 to June 2023, employing a desk review and 23 semi-structured key informant interviews with global actors from donor agencies, implementing organizations, research institutes, United Nations agencies, professional associations, and coalitions, predominantly based in the Global North. Data were analyzed using inductive thematic analysis and the research was guided by the Walt and Gibson Health Policy Triangle framework. Results Participants believe that global agenda-setting and investment decisions for MNH are primarily driven by UN agencies, donors, and implementing organizations at the global level. Although the Millennium Development Goal era successfully prioritized MNH, this focus has diminished during the SDGs, especially for HFS. Identified barriers include the complexity of reducing mortality rates in these contexts, limited political will, MNH investment fatigue, and a preference for quick wins. Fragmentation between humanitarian and development sectors and unclear mandates in protracted crises also hinder progress. Without enhanced global advocacy, accountability, and targeted investments in HFS, respondents deem global MNH targets unattainable. Conclusions While waning donor interest and the siloing of HFS in global MNH decision-making pose challenges, targeted actions to address these barriers may include designating quotas for humanitarian actors in global MNH convenings, developing shared messages that convey common interests, and adopting an equity lens. Prioritizing MNH in HFS on the global agenda demands sustained commitment to ensure these settings are not an afterthought through dedicated advocacy and accountability, high-level political engagements, global milestones, and by leveraging opportunities to capture mainstream interest. Failing to shift global priorities will result in continued stagnation and worsening MNH outcomes across HFS.